Criminal misconduct in office law and politics - Horder, Jeremy 1962- (Oxford monographs on criminal law and justice, 2018)
Democracy cannot function if the public loses faith in politicians, and that faith will be lost if politicians abuse their power with impunity. This book analyses the criminal offence of misconduct in office, and explains how it should be used, along with other measures, to hold politicians to account for abuse of their position